The Jurisdiction of the Supreme Federal Court in the Authenticity of the Final Results of the Elections and the Separation of the Membership of the House of Representatives - Hashim, Ali; Younis, Maha (Journal of Legal Sciences, 2026)
The constitutions and electoral laws in the countries of the world differ in the authority to which the task of adjudicating electoral appeals is entrusted. That the electoral appeal is no more than that his opponents are judicial in the full sense of the word. The stage of approving the election results is one of the critical and pivotal stages in the electoral process, as it has two dimensions: the first is the last stage of the first stage of nomination, election, and vote counting, and the other dimension is represented in being the beginning of the validity of membership for the winning candidate in the elections, and both dimensions entail legal and political consequences.